Engineered materials handbook - Gauthier, Michelle M. (ASM International, 1995)
If you work with polymers, ceramics, or composites, then this is the all purpose reference book you need. Culled from the four-volume Engineered Materials Handbook Series, this single desk edition provides basic property data and an outline of fabrication methods for each material. A new "Guide to Materials Selection" gives comparative property data and discusses the advantages and disadvantages of these materials for a variety of applications. There are also new sections on recycling plastics, metallizing of plastics, recycling and environmental impact of ceramics, and ceramic-matrix composites. Containing "quick study" information about the most widely used nonmetallic materials, this book gives you hundreds of well-organized tables with critical details on properties and processing. A "General Engineering Tables and Data" section provides convenient summary of facts and figures for quick reference. And you'll find numerous graphs, charts, illustrations, and photographs, plus an extensive glossary of terms.--